Folate levels modulate oncogene‐induced replication stress and tumorigenicity. Issue 9 (21st July 2015) - Lamm, Noa; Maoz, Karin; Bester, Assaf C; Im, Michael M; Shewach, Donna S; Karni, Rotem; Kerem, Batsheva
Abstract Chromosomal instability in early cancer stages is caused by replication stress. One mechanism by which oncogene expression induces replication stress is to drive cell proliferation with insufficient nucleotide levels. Cancer development is driven by alterations in both genetic and environmental factors. Here, we investigated whether replication stress can be modulated by both genetic and non‐genetic factors and whether the extent of replication stress affects the probability of neoplastic transformation. To do so, we studied the effect of folate, a micronutrient that is essential for nucleotide biosynthesis, on oncogene‐induced tumorigenicity. We show that folate deficiency by itself leads to replication stress in a concentration‐dependent manner. Folate deficiency significantly enhances oncogene‐induced replication stress, leading to increased DNA damage and tumorigenicity in vitro. Importantly, oncogene‐expressing cells, when grown under folate deficiency, exhibit a significantly increased frequency of tumor development in mice. These findings suggest that replication stress is a quantitative trait affected by both genetic and non‐genetic factors and that the extent of replication stress plays an important role in cancer development.